Hormonal changes in high-level aerobic male athletes during a sports season - Alves, J.; Toro, V.; Barrientos, G.; Bartolomé, I.; Muñoz, D.; Maynar, M. (International Journal of Environmental Research and Public Health, 2020)
The aim of this study was to determine the possible changes in plasma of several hormones such as Luteinizing Hormone, Testosterone, Cortisol and Insulin in endurance runners during the sports season. Twenty-one high-level male endurance runners (22 ± 3.2 years, 1.77 ± 0.05 m) participated in the study. Basal plasma hormones were measured at four moments during the season (initial, 3, 6 and 9 months), and were analyzed using ELISA (enzyme-linked immunosorbent assay). Testosterone and Luteinizing Hormone (LH) suffered very significant decreases (p < 0.01) at 3 months compared with the beginning and an increase (p < 0.05) at 6 and 9 months compared with 3 months. Insulin level was significantly lower (p < 0.05) at 3, 6 and 9 months compared with the initial test. Insulin and cortisol were associated inversely (r = 0.363; ß = -0.577; p = 0.017) and positively (r = 0.202; ß = 0.310; p = 0.043), respectively, with the amount of km per week performed by the runners. There was a significant association between km covered at a higher intensity than the anaerobic threshold and I (r = 0.580; ß = -0.442; p = 0.000). Our findings indicate that testosterone, LH and insulin were more sensitive to changes in training volume and intensity than cortisol in high-level endurance runners. Basal testosterone and LH concentrations decrease in athletes who perform a high volume of aerobic km in situations of low energy availability.